A second brain tumour and irradiation. - Robinson, R G (1978)
Three patients are described in whom irradiation of 2750 rad or more was used in the management of primary brain tumours, and 21 years or more later a second brain tumour of a different type occurred. One of the new tumours was a meningioma and the other two were cerebral astrocytomas. There is evidence to show that moderate doses of ionising radiations given in childhood for tinea capitis are associated with a late risk of developing a meningioma. Higher doses of radiation used for tumours in childhood are followed also by a late hazard of meningioma. There is insufficient evidence to implicate ionising radiations in the aetiology of gliomas. The oncogenic hazards of radiotherapy to the brain do not outweigh its therapeutic value in brain tumour.